Signatures of voltage dips transformer saturation and multistage dips. - Styvaktakis, E.
Obtaining information on the voltage dips that occur in a network is one of the most important tasks of a power quality monitoring program. This paper focuses on two types of voltage dips that although mentioned in the literature, their characteristics have not been presented before. These types are: voltage dips due to transformer saturation and multistage voltage dips due to faults (dips that present more than one stages of voltage magnitude before the fault clearing operation). Simulations and real measurements are used to show the features of these types of phenomena. Overall, the paper offers the means for a systematic processing of the measurements obtained by power quality monitors.
Keywords: Measurements processing; Multistage voltage dips; Power quality monitoring program; Transformer saturation; Voltage dips signatures